1997
DOI: 10.1002/(sici)1097-0142(19970715)80:2<188::aid-cncr3>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The extent of lymph node dissection for colon carcinoma

Abstract: Central lymph node dissection is not required for patients with T1 carcinomas, but proximal and distal 3-cm margins of resection are required. For T2, central lymph node dissection that includes the intermediate lymph node should be performed, as well as 5-cm proximal and distal margins of resection. For T3 and T4, central lymph node dissection including the main lymph node should be performed, as well as 7-cm proximal and distal margins of resection. [See editorial on pages 177-8, this issue.]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 6 publications
(1 reference statement)
0
25
1
1
Order By: Relevance
“…It has recently been proposed that the extent of laparoscopic lymph node dissection can be modified according to the tumor stage. In their analysis of the distribution of lymph node metastases in 164 patients with colorectal cancer, Hidu et al concluded that central lymph node dissection may not be required in those patients [7]. If these data can be confirmed, in the future less extensive laparoscopic resections can be performed for early-stage colon carcinoma as predicted by EUS.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been proposed that the extent of laparoscopic lymph node dissection can be modified according to the tumor stage. In their analysis of the distribution of lymph node metastases in 164 patients with colorectal cancer, Hidu et al concluded that central lymph node dissection may not be required in those patients [7]. If these data can be confirmed, in the future less extensive laparoscopic resections can be performed for early-stage colon carcinoma as predicted by EUS.…”
Section: Discussionmentioning
confidence: 99%
“…3 Next, we indicated the required extent of node dissection from the distribution of node metastases obtained by the clearing method on colon cancers. 4 In the present study, we tried to determine the appropriate extent of node dissection (ligation level of the tumor feeding artery and the bowel resection margin) in consideration of the site of the tumor feeding artery.…”
Section: T He Japanese General Rules For Clinical Andmentioning
confidence: 99%
“…The reason for this was the size of the reservoir. At comparative assessment of evacuation abilities in patients with short (5 cm) and "long" (10 cm) reservoirs, it was proven that patients with shorter reservoir have fewer evacuation disorders [34]. Thus, reducing the size of the reservoir made it possible to achieve the best functional results.…”
Section: Methods Of Surgical Correction Of Functional Disorders For Pmentioning
confidence: 99%